Identification of Aspergillus sp. from El-Baida marsh in Algeria: phenotypic and genotypic characterization and industrial enzyme production - Houda Sara Nacef; Rachid Belhattab (Acta Scientiarum. Biological Sciences, 2024)
The aim of this study was to compare between morphological and molecular identification methods. Two strains (A1, A2) of Aspergillus sp. isolated from El-Baida marsh, were subjected to be identified using morphological characterization, and molecular analysis performed by amplification of the ITS1 and ITS4 regions of rDNA. Morphological analysis indicated that both strains were identified as Aspergillus oryzae. However, by molecular methods A1 strain was identified as Aspergillus alliaceus and A2 strain as Aspergillus oryzae. Our results showed that phenotypic methods were insufficient for correct identification, and the use of genotypic methods is the most reliable. Enzymatic activity of the A2 isolate was evaluated using a plate assay for Lipase, Amylase and Protease production; the results illustrated the capacity of the fungus of the production of the three enzymes, which are mostly used in the production of pharmaceuticals, foods, beverages, and textile. They are found in a vast variety of sources such as animals, plants and microorganisms but microbial enzymes are more stable than the others. In addition, the reality that this fungus is known as a safe microorganism in several domains (food, beverage, cosmetic, and pharmaceutical industries), this opens the research in the future.